The fortunes and vicissitudes of Stern Whitman [large type] - Burnett, Derek, 1970- (Wheeler Publishing large print western, 2021)
"Prospector Stern Whitman and his little brother, Johnny, have made a once-in-a-lifetime strike high up in the Sierra Nevada. But once word of their claim gets out, their camp is overrun by a motley selection of fellow miners hoping to get in on the action. When one of their number is murdered, the little makeshift community devolves into two hostile factions accusing two very different suspects of the crime. So Whitman takes it upon himself to cross over the mountains and fetch back a "by-God Placerville judge" to hold an inquest and keep the peace. Accompanying Whitman on this quest are Stormy Isaac Ford, a slovenly ruffian with a reputation for violence; one of the camp's two mysterious laundresses who are known only as the Blackfoot sisters, and a self-righteous, haughty missionary and his dangerously voluptuous wife. What follows is a rollicking picaresque adventure, with Indian attacks, staggering reversals of fortune, love, betrayal, shamelessly tall tales, and a succession of colorful encounters with claim-jumpers, throat-slitting lawyers, heartbroken murderers, and even a horse hellbent on supporting the temperance movement"--"--